2023
DOI: 10.3390/md21030183
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Saccharina latissima Polysaccharides and Relation of Their Structural Characteristics with In Vitro Immunostimulatory and Hypocholesterolemic Activities

Abstract: Brown macroalgae are an important source of polysaccharides, mainly fucose-containing sulphated polysaccharides (FCSPs), associated with several biological activities. However, the structural diversity and structure–function relationships for their bioactivities are still undisclosed. Thus, the aim of this work was to characterize the chemical structure of water-soluble Saccharina latissima polysaccharides and evaluate their immunostimulatory and hypocholesterolemic activities, helping to pinpoint a structure–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
(79 reference statements)
6
5
0
Order By: Relevance
“…It was also possible to see the presence of sulphates, accounting for 5.8% of the DW of F. vesiculosus biomass (Table 1). Therefore, the carbohydrate composition herein described is consistent with the presence of different polysaccharides in F. vesiculosus, as reported for this species [11,37,38] or brown seaweeds in general [1,13,39,40].…”
Section: Fucus Vesiculosus Compositionsupporting
confidence: 90%
See 3 more Smart Citations
“…It was also possible to see the presence of sulphates, accounting for 5.8% of the DW of F. vesiculosus biomass (Table 1). Therefore, the carbohydrate composition herein described is consistent with the presence of different polysaccharides in F. vesiculosus, as reported for this species [11,37,38] or brown seaweeds in general [1,13,39,40].…”
Section: Fucus Vesiculosus Compositionsupporting
confidence: 90%
“…This fraction was revealed to be composed mainly of -SO 3 − and Fuc, corresponding to 39.3 and 18.9 mol%, respectively, showing the occurrence of fucoidans, which are commonly found in the cell walls of brown macroalgae [11,12,37,49]. The 1_RTW_Sn_D fraction was also shown to contain Glc (16.8 mol%), indicating the occurrence of laminarans, as well as uronic acids (UA, 16.1 mol%), which could be indicative of the presence of alginates or uronic acids linked to the fucoidan structure, as previously reported [13,37]. This fraction also had minor amounts of Gal, Xyl, Man, Rha and Ara, accounting together for 8.9 mol%, which may also be associated with the fucoidan structure [3,11,12].…”
Section: Recovery Of Water Soluble Polysaccharide-rich Fractionssupporting
confidence: 78%
See 2 more Smart Citations
“…The primary benefit of utilizing marine polysaccharide-based edible food packaging materials is to safeguard the food’s quality, extend its shelf life, and enhance the functional properties, financial advantages, and ecological sustainability of the packaging, as indicated by source. , Polysaccharide-based materials possess two notable advantages over conventional packaging materials, namely, their edibility and environmentally sustainable properties. , These materials are superior to those of paper, plastic, metal, and glass in this regard. Marine polysaccharides exhibit superior chemical stability and processing adaptability in comparison to packaging materials based on proteins and lipids. , Additionally, they offer a wider range of sources and are more cost-effective. Studies have indicated that materials based on polysaccharides exhibit favorable barrier properties against gases, aromas, and lipids. , Additionally, certain polysaccharides and their derivatives possess antioxidant and antimicrobial properties, which can provide effective protection to various food items such as fruits, vegetables, meat, aquatic products, nuts, confectioneries, and delicatessens, thereby prolonging their shelf life. , In addition, the development of materials based on polysaccharides serves to decrease reliance on petroleum resources, diminish the carbon footprint of the system that encompasses both the product and its packaging, and align with the strategic objectives of sustainable packaging on a global scale. , …”
Section: Introductionmentioning
confidence: 99%